THE EVALUATION OF RESPIRATORY PARAMETERS OF ROWING ATHLETES IN SINOP PROVINCE - Gökhan İpekoğlu; Erkal Arslanoğlu; Halil İbrahim Çakır; Ahmet Mor; Cansel Arslanoğlu; Kürşat Acar; Kadir Baynaz; Ozan Sever (ümit doğan üstün, 2019)
The aim of this research was to examine the respiratory parameters of elite rowing athletes in Sinop province. 15 male elit athletes participated in this research. In athletes, conditions such as not having chronic or acute disease and having no limitation of mobility due to any reason were sought. The respiratory parameters of the athletes were measured on the same day without disturbing the daily life and training program, and the lung volume and capacities were determined by COSMED Pony FX device. Measurements and tests were performed in the same time period and equal physical conditions. Mean and standard deviations of the participants were calculated by using SPSS package program. When we examine the mean values of respiratory capacity of the athletes participating in the study; The mean VC 4,29 ± 1,62, TV mean 1,21 ± 0,29, FVC mean 5,10 ± 0,81, FVC mean 107,40 ± 11,75, FEV1 mean 4,03 ± 0,83, the mean FEV1% values were 99,20 ± 15,99, the mean PEF was 6.58 ± 2.48, and the mean FEF was 3.95 ± 1.30. It is important to investigate the limits of the respiratory performance of athletes in the rowing branch related to physical competencies such as high strength, strength, and speed. Besides, performance tests including physical and anthropometric characteristics of athletes are very important in talent selection. Therefore, it is thought that the results of the study will contribute to the selection of early athletes and the studies to be carried out in this area.